Optimality Conditions and Duality for Multiobjective Variational Problems with Generalized 𝝆−(𝜼,𝜽)-B-Type-I Functions - C. Nahak (Journal of Control Science and Engineering, 2011)
We use 𝜌−(𝜂,𝜃)-𝐵-type-I and generalized 𝜌−(𝜂,𝜃)-𝐵-type-I functions to establish sufficient optimality conditions and duality results for multiobjective variational problems. Some of the related problems are also discussed.